Плаха: [роман, повесть] / Ч. Т. Айтматов - Айтматов Чингиз Торекулович (Азбука-классика, 2007)
Экземпляры: (20230511) / Инвентарный номер: 33799 / Цена: 182.30 / Сис.шифр: 84(4/8) / Авт.знак: А 36 / ГРНТИ: 17 / ББК: 84(5Кир)